Impact of drying methods on composition and functional properties of date powder procured from different cultivars. Issue 7 (4th June 2019) - Raza, Nighat; Arshad, Muhammad U.; Anjum, Faqir M.; Saeed, Farhan; Maan, Abid A.; Bader Ul Ain, Huma
Abstract: The present study was designed to evaluate the effect of two different drying methods, that is, spray drying and oven drying on physicochemical and nutritional attributes of date flesh powder of dhakki, aseel, and rabi varieties. Date powders were prepared using mixture of maltodextrin and acacia gum (50:50) as drying aid at the rate of 0.4 kg per 1.0 kg of date fruits (dry weight basis). The oven‐drying conditions were 60°C for 48 hr, whereas in spray drying, flow rate of 30 ml/min at 150°C was maintained. Date powder was obtained in both treatments from three varieties. Nutritional profile in all six powders was explored specifically with quantification of sugars using HPLC‐RI, followed by physicochemical characterization. The total phenolic compounds, color ( L * a * b * values), hygroscopicity, bulk density, wettability, solubility index, and glass transition temperatures (using differential scanning calorimetry, DSC), were determined for the date powders. The nutritional profile and total phenolic contents and sugars (sucrose, fructose, and glucose) were significantly different for the varieties, while treatments showed insignificant effect. The physicochemical characteristics of date powder varied significantly with respect to the date varieties. The colored values were affected due to treatments also, and the spray‐dried powders showed better color values. The drying methods also showed effects in some parameters such as wettability time. Similarly, bulk density was different in both treatments for rabi and aseel. The glass transition temperatures were significantly varied in varieties due to difference in sugar contents, but within the treatments, they remain unaffected. The highest glass transition temperature of spray‐dried rabi was 53.2 ± 1.31°C. Abstract : The present study was designed to evaluate the effect of two different drying methods, that is, spray drying and oven drying, on physicochemical and nutritional attributes of date flesh powder of dhakki, aseel, and rabi varieties.